Boyhood Island : My Struggle (Vol. 3) - Knausgard, Karl Ove (London Harvill Secker, 2014)
A family of four - mother, father and two boys - move to Sorland, to a new house on a new estate. It is the early 1970s, the children are small, the parents young and the future open. But at some point that future happens to them; at some point the future closes.
My Struggle (Vol. 3).
Keywords: Families -- Authors, Norwegian -- Man-woman relationships -- Autobiographical fiction